Farian Sabahi, Daniel Warner, The Osce and The Multiple Challenges Of Transition. The Caucasus and The Central Asia, Ashgate, Aldershot, 2004. - Priego Moreno, Alberto (UNISCI Discussion Papers, 2004)
Sin resumen